HDL: More Than Just Cholesterol - Anna Meilina; Andi Wijaya (The Indonesian Biomedical Journal, 2010)
BACKGROUND: Plasma concentration of high density lipoprotein cholesterol (HDL-C) are strongly, consistenly, and independently inversely associated with risk of atheroschlerotic cardiovascular disease (CVD). However, the last decade has seen several observations that do not follow this simple script.CONTENT: A proteomic analysis of HDL has given us an intriguing glimpse into novel components of HDL. HDL isolated from normal humans contains several classes of proteins, including not only apolipoproteins, but also complement regulatory proteins, endopeptidase inhibitors, hemopexin, and acute phase response proteins. These observations raise the possibility of unsuspected roles for HDL. HDL delivery of complement proteins would implicate HDL in innate immunity. Serine proteinase inhibitors would enable HDL to modulate proteolysis of the vessel wall. HDL from patients with coronary artery disease was enriched in apoE, apoC-IV, apoA-IV, Paraoxonase (PON), and complement factor C3. Highlighted additional mechanisms through which HDL protects the vessel wall are: HDL improves vascular function, decreases vascular inflammation, detoxifies radicals, and limits thrombosis.SUMMARY: Both inter- and intra-organ desynchrony may be involved in the pathogenesis of cardiometabolic disease attributable to effects in brain and multiple metabolic tissues including heart, liver, fat, muscle, pancreas, and gut. Efforts to dissect the molecular mediators that coordinate circadian, metabolic, and cardiovascular systems may ultimately lead to both improved therapeutics and preventive interventions.KEYWORDS: HDL, Apo–A1, RCT, inflammation, HDL dysfunction, HDL proteome, HDL & Apo–A1 mimetics